Comparative trends in coronary heart disease subgroup hospitalisation rates in England and Australia. Issue 17 (4th April 2019) - Nedkoff, Lee; Goldacre, Raphael; Greenland, Melanie; Goldacre, Michael J; Lopez, Derrick; Hall, Nick; Knuiman, Matthew; Hobbs, Michael; Sanfilippo, Frank M; Wright, F Lucy
Abstract : Background: Population-based coronary heart disease (CHD) studies have focused on myocardial infarction (MI) with limited data on trends across the spectrum of CHD. We investigated trends in hospitalisation rates for acute and chronic CHD subgroups in England and Australia from 1996 to 2013. Methods: CHD hospitalisations for individuals aged 35–84 years were identified from electronic hospital data from 1996 to 2013 for England and Australia and from the Oxford Region and Western Australia. CHD subgroups identified were acute coronary syndromes (ACS) (MI and unstable angina) and chronic CHD (stable angina and 'other CHD'). We calculated age-standardised and age-specific rates and estimated annual changes (95% CI) from age-adjusted Poisson regression. Results: From 1996 to 2013, there were 4.9 million CHD hospitalisations in England and 2.6 million in Australia (67% men). From 1996 to 2003, there was between-country variation in the direction of trends in ACS and chronic CHD hospitalisation rates (p<0.001). During 2004–2013, reductions in ACS hospitalisation rates were greater than for chronic CHD hospitalisation rates in both countries, with the largest subgroup declines in unstable angina (England: men: −7.1 %/year, 95% CI −7.2 to –7.0; women: −7.5 %/year, 95% CI −7.7 to –7.3; Australia: men: −8.5 %/year, 95% CI −8.6 to –8.4; women: −8.6 %/year, 95% CI −8.8 to –8.4). Other CHD rates increased in individuals aged 75–84 years in both countries. Chronic CHD comprised half of all CHD admissions, with the majority involving angiography or percutaneous coronary intervention. Conclusions: Since 2004, rates of all CHD subgroups have fallen, with greater declines in acute than chronic presentations. The slower declines and high proportion of chronic CHD admissions undergoing coronary procedures requires greater focus.